More on Beta as a Random Coefficient - Alexander, Gordon J.; Benson, P. George (Journal of Financial and Quantitative Analysis, 1982)
In their article, “Beta as a Random Coefficient, ” Fabozzi and Francis [1] present evidence which suggests that beta is a random coefficient for a “significant minority” of NYSE stocks. They obtained their evidence first, by characterizing the market model as a random coefficient model of the type described by Theil and Mennes [7], and second, by estimating its parameters for a sample of NYSE stocks over the period December 1965 through December 1971. This paper describes weaknesses in Fabozzi and Francis' implementation of the estimation procedures of Theil and Mennes [7] and Hildreth and Houck [3]. Improvements are suggested and utilized in an analysis of the returns of 683 NYSE stocks over the period January I960 through December 1971. The results of the analysis indicate that Fabozzi and Francis have overstated the case for beta being a random coefficient of the form described by Theil and Mennes.